Persepsi Masyarakat tentang Makam Raja dan Wali Gorontalo - Muhammad Rusli Ibrahim (el Harakah: Jurnal Budaya Islam, 2016)
This study aims to elucidate community perception of royal cemetry and friends of God of Gorontalo by using an approach of phenomenlogy of religion. The result of research pointed out that cemetry was interpreted as a resting place of human kinds after realm. The purpose of cemetry pilgrimage also has a variety, such as, the place of religious excursion, the efficacious place for praying, the place to get blessing from God by invoking the remains, the place to recall the goodness of a hero and a carrier of Islam, the place to learn both of  the history and Ladunni. A conducting variant procession of visiting cemetry is divided into by self-praying and praying by a priets. Particular things brought for the cemetry of Sultan Amai are for graping the water believed to have a blessing whereas pilgrims, at Ju Pangola, bring bottled water placed before cemetry and prayed by priests and also take glebe to get grace. Boon for pilgrims is:  to get a grace of life with praying for the King and Friends of God, appreciate the kindness of Islamic spreaders and Islamic heroes, and to be a guidance of life that human beings will end and return to the God. Penelitian ini bertujuan untuk mengkaji persepsi masyarakat tentang makam raja dan wali Gorontalo dengan menggunakan pendekatan fenomenologi agama. Hasil penelitian menunjukkan bahwa makam dimaknai sebagai tempat peristirahatan manusia setelah alam dunia. Adapun tujuan ziarah makam memiliki varian yakni: Makam sebagai tempat wisata religi; Tempat mustajab berdoa; Tempat untuk mendapatkan berkah dari Allah dengan mendoakan si mayit; Tempat untuk mengenang jasa pahlawan dan pembawa Islam; Tempat untuk belajar baik sejarah maupun ilmu Ladunni. Varian prosesi pelaksanaan ziarah kubur terbagi dua berdoa sendiri dan didoakan oleh imam. Adapun perlengkapan yang menyertai khususnya di makam Sultan Amai adalah mengambil air sumur yang diyakini memiliki berkah sedangkan di makam Ju Pangola adalah air mineral kemasan botol yang ditempatkan di depan makam dan didoakan oleh imam dan mengambil tanah makam untuk mendapatkan keberkahan. Hikmah bagi peziarah: untuk mendapatkan keberkahan hidup dengan mendoakan raja dan para wali Allah, menghargai jasa para pengembang Islam dan para pahlawan; serta menjadikan sebagai pelajaran hidup bahwa manusia pasti akan mati dan kembali ke Allah.